Design and analysis of solid-core microstructured optical fiber sensors for sensing surrounding refractive index and surrounding temperature - Lim, Jun Long (2018)
The microhole collapsing effect technique is a relatively simple fabrication process that produces Photonic Crystal Fiber (PCF) refractometer using modal interferometry in the range of 10−5 refractive index resolution. The repeatable method preserves the same 125 μm structural integrity of the optical fiber for various applications such as multi-parameter sensing and bioaffinity. Compared to previous reports for conventional strain or temperature sensing using a single microbubble, the use of two microbubbles in the in-line microbubble structure significantly increases the light-molecule interaction for developing ultralow concentration biosensor. It has also been demonstrated as a potential reusable and label-less PCF biosensor platform. For temperature sensing, another low-complexity approach for fabricating a PCF directional coupler structure, without costly masking or precision marking laser, is also discussed. Numerical simulations have also been investigated on the PCF directional coupler structure to validate experimental result and on the microfluidic optical fiber device to rapidly find optimal fabrication-sensitivity design.